European integration perspectives in times of global crises: 13th Network Europe Conference, Athens, 19 - 22 June 2022 - Ambühl, Michael ([EIZ Publishing], 2023)
With the White Paper on the Future of Europe, the European Commission had launched a debate on fundamental reforms of the Union structures in 2017. A total of five reform scenarios ranged from a reduction and focusing of the Union’s competences to increased integration in the sense of a United States of Europe. However, the White Paper did not have any consequences; none of the reform scenarios presented was implemented. However, current global challenges in the areas of health, climate change and energy resources as well as the shift in the global balance of power and related security issues demonstrate the increasing importance of a strong and united Europe. The idea of an “ever closer union”, as laid down in the preamble of the 1992 EU Treaty, could experience a renaissance. Against this background, the 13th Network Europe Conference addressed the importance of the integration project in times of global crises and the challenges in various policy areas, as well as the EU’s relations with its eastern and southern neighbors and its role vis-à-vis global actors such as China and Russia. This publication contains the conference contributions.